Monitoring water for conservation: A proof of concept from Mozambique - Christian, Parul; Kondylis, Florence; Mueller, Valerie; Zwager, Astrid; Siegfried, Tobias (Agricultural and Applied Economics Association, 2022)
Management of common‐pool resources in the absence of individual pricing can lead to suboptimal allocations. High‐frequency data from three irrigation schemes in Mozambique reveal patterns consistent with water inefficiency. Farmers use the amount of water required at the most sensitive stage of production as a benchmark for all allocations in the crop cycle. We demonstrate that these rule‐of‐thumb approaches create scarcity at the plot level despite schemes having sufficient water to meet farmers’ individual demands. We therefore explore the possibility of a feedback tool that visually communicates to farmers the potential to conserve by varying water applications at each stage of the crop cycle. To test the importance of tailoring the information to farmers’ own settings, we randomize a set of farmers to also receive visualizations comparing water requirements with each farmer's water use in the same season of the previous year. The experiment fails to detect an additional effect of individualized comparative feedback relative to a general information treatment. Water measurement shows that the gains from correcting observed misallocations of water in terms of water savings and avoided scarcity is potentially large as a share of water used in the agricultural sector. These findings support additional testing of feedback tools to encourage water conservation but not the expensive investments that would be required to generate feedback based on individual metering for all targeted farmers.